2013
DOI: 10.1097/nna.0b013e31827f2028
|View full text |Cite
|
Sign up to set email alerts
|

Baccalaureate Education in Nursing and Patient Outcomes

Abstract: The recommendation of the Future of Nursing report to increase RN education levels is supported by these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(139 citation statements)
references
References 23 publications
6
126
2
5
Order By: Relevance
“…These findings are consistent with Aiken's initial report over a decade ago on the relationship between nurse education and patient mortality, 6 a number of smaller studies conducted in Europe, [7][8][9][10][11] as well as with a substantial body of international reports, [12][13][14][15] including more recent studies [16][17][18][19] that continue to affirm the beneficial relationship between higher percentages of nursing staff with bachelor's degrees and lower patient mortality.…”
Section: Study On Nurse Staffing and Education And Patient Mortalitysupporting
confidence: 79%
“…These findings are consistent with Aiken's initial report over a decade ago on the relationship between nurse education and patient mortality, 6 a number of smaller studies conducted in Europe, [7][8][9][10][11] as well as with a substantial body of international reports, [12][13][14][15] including more recent studies [16][17][18][19] that continue to affirm the beneficial relationship between higher percentages of nursing staff with bachelor's degrees and lower patient mortality.…”
Section: Study On Nurse Staffing and Education And Patient Mortalitysupporting
confidence: 79%
“…국외에서는 간호사의 교육수준을 학사학위 수준으로 높 여야 한다는 (Blegen et al, 2013 (Choi J et al, 2009;Kim YI, 2010;Blegen et al, 2013). 그러나 이러한 긍정적인 측면과 더불어 학사학위과정에 있는 간호사들의 스트레스가 가중되며 (Choi J et al, 2009;Kim YI, 2010;Nam MH et al, 2013) (Seligman et al, 2006).…”
Section: 간호사의 지각된 스트레스와 신체 및 정신건강에 관한unclassified
“…Research has demonstrated a strong connection between higher levels of nursing education and higher quality patient care outcomes, fewer medication errors and lower rates of patient mortality [5,6]. Nurses with more education have demonstrated higher levels of productivity, stronger critical thinking, better clinical judgement and are more likely to take on greater professional responsibilities and complexity of practice because of their education [5].…”
Section: Trends In Rn To Bsn Educationmentioning
confidence: 99%